DINAMICA DE LA CUERDA RELATIVISTA CERCA DE UN AGUJERO NEGRO - Villegas Silva, Fulgencio (2006)
The dynamics of a string near a Kaluza-Klein black hole are studied. Solutions to the geodesic equations are obtained using the world sheet velocity of light as an expansion parameter. For a string falling into a magnetically charged black hole, it is shown that the compact dimension decreases with the world-sheet coordinate & tau;